Price performance of common stock new issues - Ibbotson, Roger G. (Journal of Financial Economics, 1975)
The paper studies both the initial and aftermarket performance (measured by risk-adjusted returns) on newly issued common stocks which were offered to the public during the 1960s. The results confirm that average initial performance is positive (11.4 percent), while the distribution of returns is skewed so that the subscriber of a single random new issue offering has about an equal chance for gain or loss. The results are generally consistent with aftermarket efficiency. Positive initial performance along with aftermarket efficiency indicate that new issue offerings are underpriced. The paper provides insights into this underpricing mystery, but does not solve it.